Lanskap Konteks Sosial-Sosietal dalam Pragmatik Berbasis Cybertexts Vaksinasi Covid-19 (Socio-Social Context Landscape in Cybertexts-Based Pragmatics Covid-19 Vaccination) - R. Kunjana Rahardi (Indonesian Language Education and Literature, 2021)
This study aims to describe the types of social-social context landscapes in cybertexts-based pragmatics related to the Covid-19 vaccination discourse. The research data is in the form of speech excerpts that contain the identity of the social-social context landscape in cybertexts. The data collection method applied is the listening method with reading and note-taking techniques. Furthermore, the data are identified, classified, and typified to apply data analysis methods and techniques. The data analysis method applied was the extra lingual equivalent method. The validity of the data used expert validation and theoretical triangulation. This study resulted in findings in the form of six types of social-social context landscapes for Covid-19 vaccination, namely (1) confirming the meaning of the speech, (2) clarifying the meaning of the speech, (3) informing the purpose of the speech, (4) setting the background for the speech, (5) supporting the meaning of the speech. the meaning of the speech, and (6) clarify the meaning of the speech.Penelitian ini bertujuan mendeskripsikan jenis-jenis lanskap konteks sosial-sosietal dalam pragmatik berbasis cybertexts terkait dengan wacana vaksinasi Covid-19. Data penelitian berupa cuplikan-cuplikan tuturan yang di dalamnya terkandung identitas lanskap konteks sosial-sosietal dalam cybertexts. Metode pengumpulan data yang diterapkan adalah metode simak dengan teknik baca dan teknik catat. Selanjutnya data diidentifikasi, diklasifikasi, dan ditipifikasi untuk dikenakan metode dan teknik analisis data. Metode analisis data yang diterapkan adalah metode padan ekstralingual. Keabsahan data menggunakan validasi pakar dan triangulasi teori. Penelitian ini menghasilkan temuan berupa enam jenis lanskap konteks sosial-sosietal vaksinasi Covid-19, yakni (1) menegaskan maksud tuturan, (2) mengklarifikasi maksud tuturan, (3) menginformasikan maksud tuturan, (4) melatarbelakangi maksud tuturan, (5) mendukung maksud tuturan, dan (6) memperjelas maksud tuturan.